Comparison of rat epidermal keratinocyte organotypic culture (ROC) with intact human skin: Lipid composition and thermal phase behavior of the stratum corneum - Pappinen, Sari; Hermansson, Martin; Kuntsche, Judith; Somerharju, Pentti; Wertz, Philip; Urtti, Arto; Suhonen, Marjukka (Biochimica et biophysica acta, 2008)
The present report is a part of our continuing efforts to explore the utility of the rat epidermal keratinocyte organotypic culture (ROC) as an alternative model to human skin in transdermal drug delivery and skin irritation studies of new chemical entities and formulations. The aim of the present study was to compare the stratum corneum lipid content of ROC with the corresponding material from human skin. The lipid composition was determined by thin-layer chromatography (TLC) and mass-spectrometry, and the thermal phase transitions of stratum corneum were studied by differential scanning calorimetry (DSC). All major lipid classes of the stratum corneum were present in ROC in a similar ratio as found in human stratum corneum. Compared to human skin, the level of non-hydroxyacid-sphingosine ceramide (NS) was increased in ROC, while α-hydroxyacid-phytosphingosine ceramide (AP) and non-hydroxyacid-phytosphingosine ceramides (NP) were absent. Also some alterations in fatty acid profiles of ROC ceramides were noted, e.g., esterified ω-hydroxyacid-sphingosine contained increased levels of oleic acid instead of linoleic acid. The fraction of lipids covalently bound to corneocyte proteins was distinctly lower in ROC compared to human skin, in agreement with the results from DSC. ROC underwent a lipid lamellar order to disorder transition ( T 2) at a slightly lower temperature (68 °C) than human skin (74 °C). These differences in stratum corneum lipid composition and the thermal phase transitions may explain the minor differences previously observed in drug permeation between ROC and human skin.